2016
DOI: 10.1007/s10856-016-5757-7
|View full text |Cite
|
Sign up to set email alerts
|

Blow-spun chitosan/PEG/PLGA nanofibers as a novel tissue engineering scaffold with antibacterial properties

Abstract: Blow spinning is continuing to gain attention in tissue engineering, as the resultant nanofibrous structures can be used to create a biomimetic environment. In this study, blow spinning was used to construct nanofiber scaffolds with up to 10 % chitosan and poly(DL-lactide-co-glycolide) in the absence or presence of poly(ethylene glycol). Scanning electron microscopy demonstrated that nanofibers were distributed randomly to form three-dimensional mats. With respect to chitosan concentration, the average fiber d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
2
17
0
1
Order By: Relevance
“…Our results by SEM characterization demonstrated that we were able to collect and fabricate, by the AJT, PLA membrane scaffolds with nanometric, random fiber structure, where the concentration of PLA exerts a direct effect on the mean diameter size of the fibers. This nanometric fiber structure could achieve the desirable functionality, mimicking the intricate interaction between cells and their microenvironment with respect to the ECM and our results are in accordance with recent studies using the AJT technology, that report similar fiber diameter structure and validate good biocompatibility properties of these spun mats . Characterization of chemical and microstructural properties of the synthesized PLA nanofiber scaffolds demonstrated that the membrane presents an amorphous structure that remain amorphous respect to the percent of concentration of the PLA solution.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results by SEM characterization demonstrated that we were able to collect and fabricate, by the AJT, PLA membrane scaffolds with nanometric, random fiber structure, where the concentration of PLA exerts a direct effect on the mean diameter size of the fibers. This nanometric fiber structure could achieve the desirable functionality, mimicking the intricate interaction between cells and their microenvironment with respect to the ECM and our results are in accordance with recent studies using the AJT technology, that report similar fiber diameter structure and validate good biocompatibility properties of these spun mats . Characterization of chemical and microstructural properties of the synthesized PLA nanofiber scaffolds demonstrated that the membrane presents an amorphous structure that remain amorphous respect to the percent of concentration of the PLA solution.…”
Section: Discussionsupporting
confidence: 90%
“…This nanometric fiber structure could achieve the desirable functionality, mimicking the intricate interaction between cells and their microenvironment with respect to the ECM and our results are in accordance with recent studies using the AJT technology, that report similar fiber diameter structure and validate good biocompatibility properties of these spun mats. 11,16,18 Characterization of chemical and microstructural properties of the synthesized PLA nanofiber scaffolds demonstrated that the membrane presents an amorphous structure that remain amorphous respect to the percent of concentration of the PLA solution. This amorphous phase is in agreement with reports that PLA treated with ethanol afford very broad peak without any sharp crystalline peaks, indicating that the ethanol is not able to induce PLA crystallization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Convincing evidence has also been presented indicating ACP as supportive of cell attachment, growth, and differentiation [29,30,31,32]. Our group has developed an alternative to traditional electrospinning by advancing airbrushing (synonymous with blow spinning) as a platform technology that is capable of synthesizing open structure nanofibers at high rates [33,34,35]. As a second objective, we focused on (1) feasibility of incorporating ACP into various polymer fibers and assessing the release of Ca and P from these composite materials; and (2) evaluation of cellular responses to these materials.…”
Section: Introductionmentioning
confidence: 99%